Myocardial strain characteristics at different interventricular pacing timings: implications for device programming and long-term clinical outcomes in patients with cardiac resynchronisation therapy. Issue 1 (2nd January 2021) - Singh, Amarnauth; Karnik, Rahool; Shah, Arti N.; Chutani, Surendra; Kantharia, Bharat K.
Abstract: Aims: Response to cardiac resynchronisation therapy (CRT) in patients with heart failure depends on the degree of correction of electromechanical dyssynchrony between the left and right ventricles (LV, RV). It is not known whether chronic programming of interventricular (VV) intervals based on characterisation of myocardial strain at different pacing intervals performed acutely would have better long-term clinical outcomes. We hence aimed to evaluate this relationship between speckle tracking strain patterns and rates at different VV intervals and long-term clinical outcomes of programmed VV pacing in patients with CRT in a prospective, longitudinal follow-up study. Methods: We assessed echocardiographic effects, myocardial strain patterns and rates in acute settings at VV intervals; 'LV Off', 'VV0', 'VV60' and 'RV Off' to provide 'RV-only', 'simultaneous BiV', 'sequential LV–RV' and 'LV-only' pacing respectively in 338 patients (age, 67.5 ± 10.3 years; male, 70%) with CRT. Thereafter, devices were programmed chronically to VV60, and long-term clinical outcomes were assessed. Results: With VV0, VV60 and LV only pacing, LVEF improved to 33.6 ± 12.3%, 40.0 ± 11.4% and 42.6 ± 11.2%, respectively, from 23.7 ± 10.2% at baseline ( p  < .001). Incremental improvement in strain occurred with VV0, VV60 and LV only pacing; greatest with LV only pacing. At 1 year, 23% patients had NYHA III-IV compared to 96% at baseline ( p  < .001). Conclusions: In patients with CRT, different VV timings show significant differences in acute myocardial strain patterns and rates, and LVEF. These changes are markedly favourable with LV-only and sequential LV–RV pacing, the latter with chronic programming also results in long-term clinical improvement.